Respuesta :

Answer:

The answer to your questions  are in bold

Step-by-step explanation:

a)  

 C = [tex]\left[\begin{array}{ccc}-6&6\\-2&4\\\end{array}\right][/tex]

    = -24 + 12

   = -12

b)  -1   7          -4   -1                   -1  - 4        7 - 1               - 5      6

    -2 -6          -8    8      =          -2 - 8       -6 + 8              -10      2

     2 -3           2   -7                  2 + 2        -3 - 7               4       -10

   -1   10         -6     5                 -1 - 6         10 + 5              -7       15